Human Leukocyte Antigen DQB1 (HLA-DQB1) Polymorphisms and the Risk for Guillain-Barré Syndrome: A Systematic Review and Meta-Analysis. - Peng-Peng Jin; Li-Li Sun; Bo-Jun Ding; Na Qin; Bin Zhou; Feng Xia; Li Li; Li-Juan Liu; Xue-Dong Liu; Gang Zhao; Wen Wang; Yan-Chun Deng; et al. (PLoS ONE)
Guillain-Barré syndrome (GBS) is an autoimmune disorder of the peripheral nervous system. There is no consensus regarding reported associations between human leukocyte antigen DQB1 (HLA-DQB1) polymorphisms and the risk for developing GBS. Here, we evaluated possible associations between HLA-DQB1 polymorphisms and the risk for GBS using a meta-analysis. We searched PubMed for case-control genetic association studies for HLA-DQB1 polymorphisms (*020x, *030x, *040x, *050x, and *060x) and the risk for GBS. Fixed-effect meta-analytical methods were used for the outcome measure and subgroup analyses. Estimated odds ratios (ORs) and 95% confidence intervals (CIs) were used to investigate the associations between HLA-DQB1 polymorphisms and the risk for GBS. Nine case-control studies involving 780 cases of GBS and 1353 controls were identified in the current study. The meta-analysis demonstrated no significant associations between HLA-DQB1 polymorphisms and the risk for GBS in Asian and Caucasian populations. There were two associations that approached significance: HLA-DQB1*030x in Asian patients (P = 0.07; OR: 0.76, 95% CI: 0.57-1.03) and HLA-DQB1*060x in all patients (P = 0.08; OR: 1.48, 95% CI: 0.96-2.29). Additional studies with larger sample sizes are required to establish a definitive assessment of the contribution of HLA-DQB1 polymorphisms to GBS risk.